Acute mountain sickness (AMS) in a Nepali pilgrim after rapid ascent to a sacred lake (4380 m) in the Himalayas - Thapa, Simant Singh (BMJ Case Rep, 2018)
A 55-year-old female Nepali pilgrim presented to the Himalayan Rescue Association Temporary Health Camp near the sacred Gosainkund Lake (4380 m) north of Kathmandu, Nepal, with a complaint of severe headache, vomiting and light-headedness. She was diagnosed with severe acute mountain sickness. Intramuscular dexamethasone was administered. Paracetamol (acetaminophen in the USA and Canada) and ondansetron were given as supportive management for headache and nausea. Arrangements were made to have her carried down by a porter immediately. After the descent, all her symptoms resolved. High-altitude pilgrims are a more vulnerable group than trekkers and mountaineers. Pilgrims generally have a rapid ascent profile, have low awareness of altitude illness and are strongly motivated to gain religious merit by completing the pilgrimage. As a result, there is a high incidence of altitude illness among pilgrims travelling to high-altitude pilgrimage sites.